Penerapan Strategi Joyfull Learning Dalam Penanaman Sikap Tanggung Jawab Siswa (Studi Kasus Pembelajaran IPS di SMP Negeri 1 Mlarak) - Arsyad Muhammad Sajjad; Muhammad Widda Djuhan (Institut Agama Islam Negeri Ponorogo, 2021)
This research was motivated by the low responsibility of students due to the assignments given by the teacher at SMP Negeri 1 Mlarak. Therefore it is necessary to implement learning strategies that are simple and fun for students so that they can instill an attitude of student responsibility. The purpose of this study was to determine the increase in student responsibility attitudes through five steps in the Joyful Learning strategy. This qualitative research carried out three techniques in data collection with interview, observation and documentation techniques. The subjects of this study were social studies teachers and students at SMP Negeri 1 Mlarak. The instruments used were interview sheets, observation and documentation of student responsibility attitudes. The results showed that the joyful learning strategy in cultivating students' responsibility towards assignments had increased, namely first, completing assignments well and on time. Second, enthusiastic and eager to accept the assignment given by the teacher.